1998
DOI: 10.1159/000011912
|View full text |Cite
|
Sign up to set email alerts
|

<i>C-myc</i> and <i>c-fos</i> in Human Osteosarcoma: Prognostic Value of mRNA and Protein Expression

Abstract: The c-myc and c-fos proto-oncogenes have several putative functions, including regulation of cell growth. In many neoplasms c-myc overexpression has been linked to poor prognosis. In order to study the role of c-myc and c-fos expression on the tumorigenesis, and the metastatic spread of osteosarcoma, frozen and paraffin-embedded tissue 38 primary osteosarcoma and 10 lung metastases were analyzed. The mRNA analysis was performed by quantitative reverse transcription-polymerase chain reaction and in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 28 publications
7
133
0
Order By: Relevance
“…For example, increased expression of the cyclin-dependent kinase, cyclin DI, has been implicated as a mechanism through which c-fos may induce bone tumor formation [32]. On the other hand, recent studies have shown that overexpression of c-fos either alone [26] or in conjunction with other oncogenes [12] is often a characteristic of osteosarcomas with metastatic potential. In these instances, high c-fos expression would appear to be related more closely to proliferation than to active matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased expression of the cyclin-dependent kinase, cyclin DI, has been implicated as a mechanism through which c-fos may induce bone tumor formation [32]. On the other hand, recent studies have shown that overexpression of c-fos either alone [26] or in conjunction with other oncogenes [12] is often a characteristic of osteosarcomas with metastatic potential. In these instances, high c-fos expression would appear to be related more closely to proliferation than to active matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…Although deregulation of c-MYC in human OS has been reported, the potential role of c-MYC in the pathogenesis of human OS is still unclear (Barrios et al, 1994;Gamberi et al, 1998). To analyze the significance Adipogenic potential regulates tumorigenic activity in OS T Shimizu et al of c-MYC expression in human OS, we examined 23 OS specimens by gene expression profiling.…”
Section: Ink4a-myc Bmscs Form Os In Syngeneic Micementioning
confidence: 99%
“…In osteosarcoma and endometrial carcinoma, c-Fos overexpression was associated with high-grade lesions and adverse outcome (Gamberi et al, 1998;Bamberger et al, 2001). In a comparative analysis between precancerous lesion of the cervix uteri and invasive cervical cancer, c-Fos expression was significantly lower in precancerous lesions (Prusty and Das, 2005).…”
mentioning
confidence: 95%